2021
DOI: 10.3390/su13158207
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Static and Dynamic Efficiency of Scientific Research of HEIs China: Three Stage DEA–Malmquist Index Approach

Abstract: Higher education institutions (HEIs) are the key to the economic and social development of a country. However, the recent advancements of higher education institutions’ universities in China have become a pivotal factor contributing to their swift growth. Considering the impact of the external environment, applying a three-stage data-envelopment analysis (DEA) and the Malmquist index method, we evaluated the static and dynamic efficiency of input–output data of scientific research produced by universities dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Since the transformation of scientific and technological achievements in universities is a complex process involving multiple indicators and stages, the stochastic frontier method is difficult to solve these difficult problems, so the non-parametric method represented by DEA has been widely used in the study of the efficiency of scientific and technological innovation in universities. For example, Xue Wuzhao et al used three-stage DEA and Malmquist index methods to evaluate static and dynamic efficiency of research input-output data of universities directly under the Ministry of Education from 2010-2017 [3]; Zhang Chonghui et al proposed a three-stage multicriteria decision making (MCDM) non-radial super-efficient data envelopment analysis with Bootstrapping [4]. Aleksandra Parteka et al studied the productivity change patterns of 266 public higher education institutions in European countries based on the Bootstrapped Malmquist index and concluded that there was a large national significance in productivity change [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the transformation of scientific and technological achievements in universities is a complex process involving multiple indicators and stages, the stochastic frontier method is difficult to solve these difficult problems, so the non-parametric method represented by DEA has been widely used in the study of the efficiency of scientific and technological innovation in universities. For example, Xue Wuzhao et al used three-stage DEA and Malmquist index methods to evaluate static and dynamic efficiency of research input-output data of universities directly under the Ministry of Education from 2010-2017 [3]; Zhang Chonghui et al proposed a three-stage multicriteria decision making (MCDM) non-radial super-efficient data envelopment analysis with Bootstrapping [4]. Aleksandra Parteka et al studied the productivity change patterns of 266 public higher education institutions in European countries based on the Bootstrapped Malmquist index and concluded that there was a large national significance in productivity change [5].…”
Section: Literature Reviewmentioning
confidence: 99%
“…When using the DEA-Malmquist index model to measure efficiency, we can not only attain the final result of efficiency level but also find out the cause of the low efficiency of the unit according to the analysis results. Finally, suggestions for optimization are put forward according to specific influencing factors [53][54][55]. Based on the above analysis, we adopted the PCA-DEA-Malmquist index model to comprehensively measure the financing efficiency of enterprises' low-carbon supply chain.…”
Section: Model Selectionmentioning
confidence: 99%
“…In 1982, Cave and other scholars measured the change of production efficiency for the first time by using the Malmquist index [28]. In 1994, Fare and other scholars improved this model, and by combining this model with the DEA method to construct the Malmquist index of total factor efficiency growth, which made the Malmquist index widely used [29]. The formula of the Malmquist index model is shown below.…”
Section: Malmquist Indexmentioning
confidence: 99%